2020
DOI: 10.1038/s41598-020-60888-5
|View full text |Cite
|
Sign up to set email alerts
|

A competent bidrug loaded water soluble chitosan derivative for the effective inhibition of breast cancer

Abstract: Drug resistance and damage caused to the normal cells are the drawbacks which have limited the use of the existing effective anticancer drugs. Attainment of a steady and extended release by encapsulating dual drugs into biocompatible and biodegradable vehicles is the key to enable the use of these drugs for effective inhibition of cancer. In this study, carboxymethyl chitosan (CMCS), a proficient water-soluble derivative of chitosan has been synthesized using chemical route and used for the delivery of 5-Fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Figure 5C, the presence of 45.64% oxygen, 25.91% carbon, 4.14% nitrogen, 14.42% phosphorous, and 9.81% calcium provided evidences that Cs, Alg and their respective crosslinkers are present in the NCs 56–58 . Similar to Cs‐Alg/IO 5FU NCs, all elements were present with the addition of 2.23% iron, and fluorine were present in both NCs indicating that the 5FU was successfully loaded into the IPN of NCs 59,60 …”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Figure 5C, the presence of 45.64% oxygen, 25.91% carbon, 4.14% nitrogen, 14.42% phosphorous, and 9.81% calcium provided evidences that Cs, Alg and their respective crosslinkers are present in the NCs 56–58 . Similar to Cs‐Alg/IO 5FU NCs, all elements were present with the addition of 2.23% iron, and fluorine were present in both NCs indicating that the 5FU was successfully loaded into the IPN of NCs 59,60 …”
Section: Resultsmentioning
confidence: 86%
“…[56][57][58] Similar to Cs-Alg/IO 5FU NCs, all elements were present with the addition of 2.23% iron, and fluorine were present in both NCs indicating that the 5FU was successfully loaded into the IPN of NCs. 59,60 3.4 | Particle sizes, zeta potential and PDI…”
Section: Field Emission Scanning Electron Microscopy With Energy Disp...mentioning
confidence: 99%
“…Maximum frequencies for aliphatic C–H stretching are reported by Nivethaa et al. [ 36 ] to be 2900 cm −1 , for N–H bending to be 1662 cm −1 , for primary alcoholic C–O stretching to be 1414 cm −1 , and for hydroxyl group C3 stretching to be 1098 cm −1 . Tq-CsNPs size distribution as a function of reported intensity.…”
Section: Resultsmentioning
confidence: 96%
“…The findings of those studies indicated that 5-FU loaded into polymers was effective at inhibiting MCF-7 breast cancer cells’ growth and proliferation, albeit in a concentration-dependent manner. Additionally, 5-FU and doxorubicin drug encapsulation displayed high cytotoxicity, suggesting the possibility of combinations of drugs in the treatment of multiple types of cancer, including BC [ 38 ]. Christensen et al stated that TP53-mutated BC accumulated more 5-FU mutations than TP53 wild type BC [ 39 ].…”
Section: Discussionmentioning
confidence: 99%